What do examiners look for in a PhD thesis? Explicit and implicit criteria used by examiners across disciplines. Issue 8 (14th November 2022) - Chetcuti, Deborah; Cacciottolo, Joseph; Vella, Nicholas
Abstract: Achieving a PhD degree is viewed by academic institutions as a major landmark of success and achievement. It gives recognition to researchers and provides entry into academia. A PhD degree is not awarded lightly and doctoral candidates undergo a rigorous examination process. This study seeks to gain a better understanding of the way in which examiners go about assessing doctoral work. Data for the study included written examiner reports presented to the University of Malta from four different faculties: Arts, Education, Science and Medicine & Surgery for the years 2017-2018. The findings suggest that the doctoral examination is a social practice with examiners using a combination of explicit criteria outlined in the University of Malta regulations, and implicit criteria based on their own personal expectations. Using a combination of these criteria, examiners look for doctoral work that makes a contribution to knowledge, is critical and analytical and is not marred by typographical or grammatical errors. The study also highlights a number of disciplinary differences in the expectations of examiners in different faculties and the need for more formal professional development for examiners to ensure a shared interpretation of criteria within a community of assessors.